Revealing the Colonial Hypocrisy: Racism and Identity on This Earth of Mankind - Ryan, Patrick Maullana; Darmawan, Ruly Indra (Universitas Negeri Semarang, 2025)
This Earth of Mankind, a powerful literary work that explores the complexities of identity and the aftereffects of colonial domination, was published in 1980 by Indonesian author Pramodya Ananta Toer. The intricate web of power dynamics present in colonial nations is shown by the novel's examination of oppression. The story sheds light on the racial and social hierarchy that uphold the systematic oppression of the indigenous population, as well as the stark disparities that exist between the colonizers and the colonized. This essay highlights the diverse aspects of identity formation in a colonial setting. The novel's analysis of oppression demonstrates the complex web of power relations that existed in colonial countries. The narrative highlights the glaring differences between the colonizers and the colonized, as well as the racial and socioeconomic hierarchy that sustains the systematic subjugation of the indigenous population. It revolves around Minke, a native Javanese character who struggles with his multiple identities as an educated man navigating a Dutch-dominated society and as a representative of his indigenous culture. The various facets of identity creation in a colonial context are highlighted in this essay.